Muslim Women Education and Izālah Movement in Kaduna State of Nigeria - Abdullatif, Bashir; Sharif, Mohd Farid Mohd (European Publisher, 2019)
This paper aims to examine Islamic education classes for Muslim married women founded by the reformist Islamic movement, Jamā'tul Izālatil bid' ah Wa Ikāmatis Sunnah (the Society for Removing Islamic Innovation and Restoring Practices of Prophet Muhammad SAW), known as Izālah in the Zaria town of Kaduna state Nigeria, as expanding Islamic education is one of its key goals. Many western scholars cannot differentiate between Islamiyyah schools and traditional Qur'anic school's whose syllabus is solely restricted to the routine learning of the Glorious Qur'an. This phenomenon has led to some problems. This paper aims to describe the impact of Islamiyyah schools on Muslim women's lives, especially in Kaduna State Zaria, and to address Izālah's role in establishing Islamiyyah classes for married women. The paper uses a qualitative research method design. Interviews were conducted with those schools headmaster and married women; qualitative data were provided. This paper reveals that Islamiyyah schools for women are very vital to the understanding and performance of Islamic ritual practices. Yes, Islamiyyah schools teach Muslim women on how to worship Allah and have played a significant role not only in Kaduna State education but also in the country at large.